Primary Progressive Aphasia as a Prodromal State of Dementia With Lewy Bodies: A Case Report - Watanabe, Hiroyuki; Ikeda, Manabu; Mori, Etsuro (Frontiers in Neurology, 2020)
Dementia with Lewy bodies (DLB) is the second most common form of dementia in the elderly, and various clinical symptoms, including olfactory dysfunction, dysautonomia, depression, and rapid eye movement sleep behavior disorders (RBD), occur in patients with the prodromal state of DLB. We herein describe a case of a 72-years-old right-handed woman who exhibited primary progressive aphasia (PPA) as a prodromal state of DLB and took cholinesterase inhibitors (donepezil). At 4.5 years after aphasia onset, she exhibited all the core clinical features of DLB, including visual hallucinations, fluctuating cognition, RBD, and Parkinsonism, as well as progressive language impairment. She showed reduced dopamine transporter (DAT) uptake (assessed by DAT single-photon emission computed tomography imaging) in the striatum and decreased cardiac uptake (determined by 123I-metaiodobenzylguanidine myocardial scintigraphy), which are indicative biomarkers of DLB. Thus, this patient met all the criteria for probable DLB. Notably, the unique feature of this case was the presentation of PPA, which is seldom observed in typical DLB. Moreover, cholinergic enhancement (donepezil, 5 mg daily) improved her language function and global cognitive function, although mild aphasia remained. The findings provide valuable insights into the spectrum of the prodromal state of DLB and shed light on the development of the medication for PPA caused by cholinergic insufficiency.